Macrophage-myofibroblast transition as a novel therapeutic target in shoulder stiffness: multi-omics study and experimental validation - Qi, Beijie; Yu, Weihan; Wang, Hanyi; Li, Yuqi; Deng, Shuang; Yi, Chengqing (Frontiers in Cell and Developmental Biology, 2026)
BackgroundShoulder stiffness (SS) is a fibrotic disease with pain and reduced range of motion (ROM). The pathogenesis of SS remains unclear. Recent studies reveled that macrophage-myofibroblast transition (MMT) is an important mechanism underlying fibrogenesis, but whether MMT was involved in SS progression remained unknown. This study aimed to clarify the role of MMT in SS pathogenesis, and to evaluate the efficacy of MMT-targeted therapy.MethodsShoulder capsules from SS patients were collected, and the mouse SS model was established. Western blot and immunofluorescence were utilized to detect protein expression. Multi-omics analysis was performed in order to identify the potential pathogenic factor. Histological and biomechanical analysis was conducted for the in vivo experiments.ResultsSignificant capsule fibrosis and ROM restriction were observed in both SS patients and SS mice. Upregulated MMT was detected in SS capsules. Multi-omics analysis identified periostin (POSTN) as the potential pathogenic factor. MMT was induced by POSTN in vitro. POSTN knockdown effectively attenuated MMT in mouse SS models, ameliorating capsule fibrosis and improving ROM.ConclusionIn this study, we proved that MMT was involved in SS progression, and identified POSTN as the key regulator of MMT. POSTN knockdown effectively suppressed MMT, alleviated fibrosis, and restored ROM in vivo. This research elucidated a novel mechanism in SS pathogenesis and developed POSTN as a promising therapeutic target for SS.